Philip Potter: Faith and Action - Sjollema, Baldwin (The ecumenical review, 2018)
This article reviews the role of Philip Potter as general secretary of the World Council of Churches (1972-1984), highlighting his background in the Caribbean, his involvement in mission, and his support for the Programme to Combat Racism. In doing so, it considers those issues to which Potter was deeply committed, including the fundamental unity of Christian witness and service, the correlation of faith and action, and the inseparable connection between the personal spiritual life of Christian believers and their obedient action in the world.